GAMBARAN AKTIVITAS FISIK DAN KEJADIAN OBESITAS DI PUSKESMAS MINANGA KOTA MANADO - Roring, Marlen Lestari; Rambitan, Mesak; Telew, Agusteivie (Yayasan Syalom Cipta Sumikolah, 2024)
The aim of this research was to determine the description of physical activity and the incidence of obesity in the Minanga health center, Manado city. Using quantitative research methods with a descriptive analytical approach, namely to describe and explain in more depth the variables of physical activity and obesity, this research was conducted in July-August 2023 in the working area of the Minanga health center, Manado city. To understand the picture of physical activity and the incidence of obesity in the Minanga health center, Manado city, research was conducted on 25 people suffering from obesity in the Minangan health center working area, Manado city, using an instrument in the form of a questionnaire. In this research, the data that has been collected is processed and analyzed using a computer using Ms. software. Excel and SPSS. From the results obtained, it can be concluded that physical activity, 16 respondents with light physical activity (64%), 5 people with moderate physical activity (20%) and 4 people with heavy physical activity (16%). The majority of respondents predominantly do light physical activity rather than moderate and heavy physical activity. And obesity, 4 people are classified as type I obesity and 21 people are classified as type II obesity. The type of obesity that most respondents suffer from is type II obesity. The tendency for type II obesity is also related to the respondent's physical activity.